The role and mechanism of the NLRP3-IL-1β/IL-18 signaling axis in the progression of sepsis under an aging phenotype - Xu, Chuchu; Zhu, Renjun; Dai, Qingfeng; Xu, Guangen; Zhang, Guolin (Life sciences (1973), 2025)
To investigate the impact of age on sepsis outcomes and explore potential therapeutic targets using the mouse model. Sepsis was induced via cecal ligation and puncture (CLP) in naturally aged mice (18 months) and young mice (3 months). Sepsis severity, mortality rates, bacterial loads, and cytokine levels (IL-18 and IL-1β) were compared between the two groups. NLRP3 expression was analyzed in various organs. Additionally, NLRP3 inhibitor MCC950 and specific antibodies against IL-18 and IL-1β were administered to assess their therapeutic effects. Note: This study was partially based on human samples. Aged mice demonstrated more severe sepsis symptoms and increased mortality compared to young mice. Elevated levels of IL-18 and IL-1β were observed in aged septic mice, indicative of augmented NLRP3 inflammasome activation. Human data corroborated these findings, showing higher serum levels of IL-18 and IL-1β in older sepsis patients. Treatment with NLRP3 inhibition (MCC950) and antibodies against IL-18 and IL-1β alleviated sepsis symptoms in aged mice, suggesting these pathways as potential therapeutic targets. The study highlights the critical role of the NLRP3-IL-18/IL-1β axis in age-related disparities in sepsis outcomes and suggests potential therapeutic targets for improving outcomes in aged sepsis patients. •Aged mice exhibit worse sepsis outcomes vs. young mice in a CLP-induced sepsis model.•Aging amplifies NLRP3 inflammasome activation, driving elevated IL-18/IL-1β levels in septic aged mice and human patients.•NLRP3 inhibition (MCC950) reduces sepsis severity in both aged and young mice, narrowing age-related outcome disparities.•IL-18/IL-1β antibody blockade reverses exacerbated sepsis in aged mice.•Targeting the NLRP3-IL-18/IL-1β axis emerges as a promising therapeutic strategy for aged sepsis patients.